Sex, Lies and TV: Censorship and Subtitling - Scandura, Gabriela (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThe following article deals with censorship and subtitled television programs. It is divided into three parts. The first part describes the reasons for censorship, including self-censorship. The second part explains the different types of censorship and gives examples of each, and the third part tries to explain the findings of a survey regarding audience awareness of subtitling censorship and reception of restrictions such as the use of a ‘Latin American’ Spanish.